2017
DOI: 10.1155/2017/6842938
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Geometry Design Parameters on the Static Strength and Dynamics for Spiral Bevel Gear

Abstract: Considering the geometry design parameters, a quasi-static mesh model of spiral bevel gears was established and the mesh characteristics were computed. Considering the time-varying effects of mesh points, mesh force, line-of-action vector, mesh stiffness, transmission error, friction force direction, and friction coefficient, a nonlinear lumped parameter dynamic model was developed for the spiral bevel gear pair. Based on the mesh model and the nonlinear dynamic model, the effects of main geometry parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Though the differences appear to be small, they can be quite significant, because the durability service life of gears is strongly dependent on contact stress. For instance, Feng and Song [13] found that a 4.76% decrease in the contact stress of a steel spiral bevel gearset increased the pitting service life by 44%. Consequently, there is a need to determine the maximum contact stress in gear meshes with reasonable accuracy because a small decrease in contact stress can significantly increase the pitting service life of a gearset.…”
Section: Fig 4: Gear Contact Stress Form Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Though the differences appear to be small, they can be quite significant, because the durability service life of gears is strongly dependent on contact stress. For instance, Feng and Song [13] found that a 4.76% decrease in the contact stress of a steel spiral bevel gearset increased the pitting service life by 44%. Consequently, there is a need to determine the maximum contact stress in gear meshes with reasonable accuracy because a small decrease in contact stress can significantly increase the pitting service life of a gearset.…”
Section: Fig 4: Gear Contact Stress Form Factormentioning
confidence: 99%
“…According to Feng and Song [13], spiral bevel gears have very complex tooth geometries and kinematics. Unlike cylindrical gears, the mesh point, mesh force, and line-of-action vector for spiral bevel gears are time varying quantities in 3D space.…”
Section: Introductionmentioning
confidence: 99%
“…e results show that with the variety of the meshing frequency, the system enters into chaos through period-doubling bifurcation; with the variety of the support stiffness, the system changes into chaos through quasi-period bifurcation; and in the process of the meshing frequency varying, jump phenomena exist in the system. Feng and Song [2] considered the time-varying meshing force of the gear, the position of the meshing point, the transmission error, the direction of the friction force, and the friction coefficient, and then established a dynamic model of concentrated parameters. On this basis, the effects of the dynamic meshing force and dynamic transmission error on the system response are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Yinong et al [15] studied the effect of the asymmetric mesh stiffness on the 8-DOF spiral bevel gear transmission system. Feng and Song [16] investigated the effects of the dynamic meshing force and dynamic transmission error.…”
Section: Introductionmentioning
confidence: 99%